Effects of intraoperative low dose ketamine on remifentanil-induced hyperalgesia in gynecologic surgery with sevoflurane anesthesia - Hong, Boo Hwi (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: Remifentanil is useful during general anesthesia because of its rapid onset and short acting time. However, some studies report that due to opioid-induced hyperalgesia (OIH) and tolerance, remifentanil also increases early postoperative pain. The occurrence of OIH and opioid-induced tolerance is mainly thought to be due to central sensitization by the activation of NMDA receptors. Therefore, we investigated the effects of continuous infusion of ketamine, an NMDA receptor antagonist, on postoperative pain and the quantity of opioids used. METHODS: 40 patients scheduled to undergo laparoscopic gynecologic surgery were randomly allocated into two groups. Anesthesia was equally maintained with sevoflurane and 4 ng/ml of remifentanil in all patients. Ketamine (0.3 mg/kg) was injected and followed with a continuous dosage of 3 µl/kg/min in the ketamine group (n = 20) while the control group was injected and infused with an equal amount of normal saline. We compared postoperative VAS up to 7 hours and morphine demand through PCA. RESULTS: Postoperative VAS and morphine demand was significantly lower in the ketamine group 2 and 3 hours after surgery, respectively. CONCLUSIONS: When general anesthesia is maintained with sevoflurane and remifentanil in patients undergoing laparoscopic gynecologic surgery, continuous infusion of low dose ketamine decreased early postoperative pain and the quantity of opioids used.